2019
DOI: 10.1002/sim.8342
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the quality of optimal treatment regimes

Abstract: When multiple treatment alternatives are available for a disease, an obvious question is which alternative is most effective for which patient. One may address this question by searching for optimal treatment regimes that specify for each individual the preferable treatment alternative based on that individual's baseline characteristics. When such a regime has been estimated, its quality (in terms of the expected outcome if it was used for treatment assignment of all patients in the population under study) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
(69 reference statements)
0
4
0
Order By: Relevance
“…This issue will go with questions on the quality of the estimator that may be picked for this purpose. Otherwise, further advancing this issue, also making correct inferences about the quality on the level of the population of an estimated OTR (Sies & Van Mechelen, 2019) (as well as about the difference in such quality between different estimated OTR's) is a critical inferential issue, which, in part, is an open problem that may be considered a challenge for further statistical research.…”
Section: Discussionmentioning
confidence: 99%
“…This issue will go with questions on the quality of the estimator that may be picked for this purpose. Otherwise, further advancing this issue, also making correct inferences about the quality on the level of the population of an estimated OTR (Sies & Van Mechelen, 2019) (as well as about the difference in such quality between different estimated OTR's) is a critical inferential issue, which, in part, is an open problem that may be considered a challenge for further statistical research.…”
Section: Discussionmentioning
confidence: 99%
“…However, for the purpose of building a decision rule for allocating patients to their optimal treatment, it is important to evaluate the benefit of such an allocation (e.g., compared with a random allocation). To this end, several estimators have been developed (Sies & Mechelen, 2019) and call for evaluation within the frame of psychotherapy research.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…We refer the reader to [14] and [16] for a discussion of considerations and best practices when implementing the ODTR SuperLearner. Obtaining inference for the mean outcome under the ODTR has been shown to be difficult due to its lack of smoothness [6,9,29]; however, several methods have been proposed for constructing valid confidence intervals for this parameter, such as re-sampling techniques [6,30,31]. One approach to inference is to rely on parametric models; however, misspecification of these models can bias results.…”
Section: Introductionmentioning
confidence: 99%
“…Both [27] and [17] found that, indeed, there exists a positive finite sample bias when using TMLE versus CV-TMLE when estimating the value of the ODTR; in other words, with the rule learned and evaluated on the same data, estimates of the value of the rule may be optimistic, and CV-TMLE corrects this bias. Additionally, recently, [34] showed that cross-validation techniques for estimating the value of the rule, and in particular CV-TMLE, yielded a smaller difference between the true expected value under the true rule and its estimate, versus, for example, bootstrap techniques for evaluating a rule.…”
Section: Introductionmentioning
confidence: 99%